The extent to which TOEFL iBT speaking scores are associated with performance on oral language tasks and oral ability components for Japanese university students. (January 2015) - Ockey, Gary J.; Koyama, Dennis; Setoguchi, Eric; Sun, Angela
The purpose of this study was to determine the extent to which performance on the TOEFL iBT speaking section is associated with other indicators of Japanese university students' abilities to communicate orally in an academic English environment and to determine which components of oral ability for these tasks are best assessed by TOEFL iBT. To achieve this aim, TOEFL iBT speaking scores were compared to performances on a group oral discussion, picture and graph description, and prepared oral presentation tasks, and their component scores of pronunciation, fluency, grammar/vocabulary, interactional competence, descriptive skill, delivery skill, and question answering. Participants were Japanese university students ( N = 222), who were English majors in a Japanese university. Pearson product–moment correlations, corrected for attenuation, between scores on the speaking section of TOEFL iBT and the three university tasks indicated strong relationships between the TOEFL iBT speaking scores and the three university tasks and high or moderate correlations between the TOEFL iBT speaking scores and the components of oral ability. For the components of oral ability, pronunciation, fluency, and vocabulary/grammar were highly associated with TOEFL iBT speaking scores while interactional competence, descriptive skill, and delivery skill were moderately associated with TOEFL iBT speaking scores. The findings suggest that TOEFL iBT speaking scores are good overall indicators of academic oral ability and that they are better measures of pronunciation, fluency and vocabulary/grammar than they are of interactional competence, descriptive skill, and presentation delivery skill.